The formalization of social-science research ethics: How did we get there? - Sleeboom-Faulkner, Margaret; Simpson, Bob; Burgos-Martinez, Elena; McMurray, James (HAU journal of ethnographic theory, 2017)
In the United States, the “common law,” that regulates ethics review is being overhauled. We ask how UK University Research Ethics Committees (U-RECs), following the American model, have been able to shape social-science research without much commotion, and whether it is time for change. Despite the misbehavior of some ethnographic researchers, most social science research is valued for and motivated by its expert engagement with moral questions regarding discrimination, unfairness, exploitation, and so on, at home and abroad: knowledge of and sensitivity to the complexities around the violation of socio-economic, political, and cultural norms and values are carried high in the social science banner. Yet, since the 1990s, social science research projects in the Anglo-American world have increasingly entrusted research ethics to the scrutiny of U-RECs. This ethical delegation gives a mandate to U-RECs, often without suitable expertise, to vet research projects in a bureaucratic and time-consuming manner. It does not just lead to misunderstandings and frustration; it also privileges research as defined by research ethics committees rather than in negotiation with the ethics we encounter “in the field.” Although formal research ethics is clearly confusing early career researchers (and others!) about the role of ethics (which?), its forms have come to shape our disciplines. How did we get there? How do we move forward?